Behavior of Reduced Beam Section Moment Connection with Varying Thickness of Continuity Plate - Berde, Neha K; Awari, Uttam R.; Kulkarni, Swati A (International Journal of Sustainable Construction Engineering and Technology, 2017)
Reduced beam section (RBS) connection is investigated and is widely used in US, Japan and Europe. However, very limited study is conducted with respect to Indian profiles. This study is conducted to give advantageous factors related to RBS connections with continuity plate (CP) and to learn usefulness of those connections for Indian sections. Analytical work of reduced beam section moment connections by providing continuity plates of varying thickness under monotonic drift is presented in this paper. The model is created with finite element method (FEM) and analyzed by ANSYS workbench 16.0 software. Observations were noted for the connections with varying thickness of continuity plates and without continuity plates respectively. Similarity of the results is observed between the, the connections with CP having same thickness of beam flange and with CP having half the thickness of beam flange